Some approximation properties of bivariate q-Stancu-Beta operators - Mohammad Mursaleen,; Faisal Khan,; Asif Khan,; Kilicman, Adem (Hindawi Publishing Corporation, 2014)
We use q-integers to construct bivariate q-Stancu-Beta operators and establish weighted A-statistical approximation properties for these operators. Further, we estimate the rate of the point wise convergence of the proposed operators by means of bivariate modulus of continuity.